Java 正则表达式替换的示例

概要:

Java 正则表达式替换的示例

| |目录

正文

package regex;
import java.util.regex.*;
import java.io.*;
public class Regex {
	
	public static void main(String [] args) {
		String s = "12+3*(2+4)-4*7-1.21";
		Pattern pattern = Pattern.compile("\d+(\.\d+|\d*)");
		StringBuffer sb = new StringBuffer();
		Matcher matcher = pattern.matcher(s);
		double [] numbers = new double[26];
		int i = -1;
		while (matcher.find()) {
			i++;
			numbers[i] = Double.valueOf(matcher.group());
			matcher.appendReplacement(sb, ""+(char)('A'+i));
		}
		matcher.appendTail(sb);
		System.out.println(sb);
	}
		
}

输出结果:A+B*(C+D)-E*F-G

来源

来自CSDN博客:Java正则表达式替换的示例

评论关闭
评论 还能输入200
评论关闭
评论 还能输入200
资料加载中...
已关注 , 取消